2018
DOI: 10.1002/ece3.3933
|View full text |Cite
|
Sign up to set email alerts
|

The temperature‐size rule in Daphnia magna across different genetic lines and ontogenetic stages: Multiple patterns and mechanisms

Abstract: Ectotherms tend to grow faster, but reach a smaller size when reared under warmer conditions. This temperature‐size rule (TSR) is a widespread phenomenon. Despite the generality of this pattern, no general explanation has been found. We therefore tested the relative importance of two proposed mechanisms for the TSR: (1) a stronger increase in development rate relative to growth rate at higher temperatures, which would cause a smaller size at maturity, and (2) resource limitation placing stronger constraints on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 53 publications
0
26
1
Order By: Relevance
“…Whether the OST and TSR share the same biological drivers is unclear (Efford ; Yampolsky & Scheiner ; Hoefnagel et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Whether the OST and TSR share the same biological drivers is unclear (Efford ; Yampolsky & Scheiner ; Hoefnagel et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…From September 2014, we stimulated hatching by exposing the eggs to light and 20°C. The eggs were checked daily, and neonates were placed in individual 100‐ml tubes, held in Dutch Standard Water (DSW; Hoefnagel, de Vries, Jongejans, and Verberk ()) (200 mg/L CaCl 2 .2H 2 O, 180 mg/L MgSO 4 .7H 2 O, 100 mg/L NaHCO 3 , 20 mg/L KHCO 3 ; NEN6503 ()) and fed with instant algae (1.6 × 10 5 cells/ml; Shellfish 1800, Reed Mariculture). Medium, containing new food, was refreshed three times per week.…”
Section: Methodsmentioning
confidence: 99%
“…Note that lineages L, A3 and A4 are referred to as C, D and E, respectively, by Hoefnagel et al. ().…”
Section: Methodsmentioning
confidence: 99%
“…These individual effects have been shown to scale up to destabilize population dynamics and increase the risk of extinction (Bestion et al, 2015). For example, many studies have shown that body size shrinkage is mediated by genetic background (Cambronero, Beasley, Kissane, & Orsini, 2018;Hoefnagel, Vries, Jongejans, & Verberk, 2018), pesticides (Cambronero et al, 2018), and food availability (Cambronero et al, 2018;Heugens et al, 2001;Orcutt & Porter, 1984). However, the effect of temperature on organismal fitness often depends on several other ecological factors.…”
mentioning
confidence: 99%